Markov Chain‐Based Stochastic Modeling of Deep Signal Fading: Availability Assessment of Dual‐Frequency GNSS‐Based Aviation Under Ionospheric Scintillation. Issue 9 (17th September 2021) - Sun, Andrew K.; Chang, Hyeyeon; Pullen, Sam; Kil, Hyosub; Seo, Jiwon; Morton, Y. Jade; Lee, Jiyun
Abstract: Deep signal fading due to ionospheric scintillation severely impacts global navigation satellite system (GNSS)‐based applications. GNSS receivers run the risk of signal loss under deep fading, which directly leads to a significant decrease in navigation availability. The impact of scintillation on GNSS‐based applications can be mitigated via dual‐frequency signals which provide a backup channel. However, the benefit of dual‐frequency diversity highly depends on the correlation of fading processes between signals at different frequencies. This paper proposes a Markov chain‐based model that simulates the actual behavior of correlated fading processes in dual‐frequency channels. A set of recorded scintillation data was used to capture transitions among all fading states based on the fading and recovery of each signal frequency. A statistical study of deep fading characteristics in this data revealed that the Markov chain‐based model accurately generates realistic correlated fading processes. Using the proposed model, aviation availability of localizer performance with vertical guidance down to a 200‐foot decision height ("LPV‐200") under a strong scintillation scenario is analyzed by considering the effects of signal outages due to deep fading. A parametric analysis of the availability resulting from variations in mean time to loss of lock, mean time to reacquisition, and ionospheric delay uncertainty was conducted to investigate the performance standards on GNSS‐based aviation under scintillation. The analysis results demonstrate a significant benefit of frequency diversity on aviation availability during scintillation. This model will further enable the assessment of GNSS‐based availability for aviation and other applications under a full range of scintillation conditions. Plain Language Summary: One of the most detrimental impacts of space weather on GNSS‐based navigation applications is ionospheric scintillation in equatorial region, which can cause deep and frequent signal fading on GNSS signals. In particular, GNSS navigation may be lost when multiple satellites are briefly unusable for GNSS receiver calculations due to the signal fades caused by scintillation. The use of dual‐frequency signals can diminish the impact of scintillation by providing a backup ranging source on one frequency. However, frequency diversity is only partially helpful because the effect of scintillation is correlated across frequencies, meaning that a receiver may still lose satellites when their signals on both frequencies are simultaneously plagued by deep fading. Here we propose a new stochastic model to represent a more accurate description of correlated fading processes observed in actual scintillation data. We incorporate scintillation effects into a simulation of aviation availability. The simulation results provide estimates of the impact of scintillation on L1 single and L1/L5 dual‐frequency aviation availability and quantify the benefit from the use of dual‐frequency signals during strong scintillation. Further development of this model will enable the assessment of effects from other scintillation conditions and scenarios on availability for aviation and other applications of GNSS. Key Points: Deep fades observed in a Global Positioning System (GPS) L1/L5 strong scintillation data set have been characterized in terms of availability for global navigation satellite system (GNSS) navigation A stochastic model based on a Markov chain accurately generates realistic correlated fading processes of GNSS signals under scintillation New Markov chain model confirms that use of dual‐frequency GNSS signals significantly enhances aviation availability during scintillation